Regional trade agreements: What do we know and what do we miss? - Mario Larch; Yoto Yotov (FIW - Research Centre International Economics, 2024)
Regional Trade Agreements (RTAs) are a widespread and common tool to facilitate trade of goods and services between countries. While they targeted originally goods trade and mainly tariffs, today, RTAs are much more comprehensive, covering also services and going far beyond eliminating tariffs by harmonizing non-tariff measures and agreeing on policies in a wide area of fields, such as foreign investments, labour markets, protection of intellectual property rights, and the environment. In this policy brief, we first discuss the current state of knowledge concerning the quantification of the effects of RTAs on international trade, and then highlight shortcomings of the standard approach to measure the impact of RTAs opening up potential avenues for future research and policy work in this area.
Keywords: 330